Applied process design for chemical and petrochemical plants. [Volume 3] - Ludwig, Ernest E. (Houston : Gulf Pub. Co., 1995)
This third edition of Applied Process Design for Chemical and Petrochemical Plants, Volume 3, is completely revised and updated throughout to make this standard reference more valuable than ever. It has been expanded by more than 200 pages to include the latest technological and process developments in heat transfer, refrigeration, compression and compression surge drums, and mechanical drivers. Like other volumes in this classic series, this one emphasizes how to apply techniques of process design and how to interpret results into mechanical equipment details. It focuses on the applied aspects of chemical engineering design to aid the design and/or project engineers in rating process requirements, specifying for purchasing purposes, and interpreting and selecting the mechanical equipment needed to satisfy the process functions. Process chemical engineering and mechanical hydraulics are included in the design procedures. Includes updated information that allows for efficiency and accuracy in daily tasks and operations Part of a classic series in the industry.
Vol. 1. Emphasizes how to apply techniques of process design and interpret results into mechanical equipment details.
Vol. 3 published: Boston : Gulf Professional Pub.
Includes bibliographical references and indexes.
Keywords: Chemical plants -- Equipment and supplies; Petroleum industry and trade -- Equipment and supplies; Electronic books